Increasing temperature elevates the variation and spatial differentiation of pesticide tolerance in a plant pathogen - Lurwanu, Yahuza; Wang, Yan-Ping; Wu, E-Jiao (Wiley, 2021)
Climate change and pesticide resistance are two of the most imminent challenges human society is facing today. Knowledge of how the evolution of pesticide resistance may be affected by climate change such as increasing air temperature on the planet is important for agricultural production and ecological sustainability in the future but is lack in scientific literatures reported from empirical research. Here, we used the azoxystrobin-Phytophthora infestans interaction in agricultural systems to investigate the contributions of environmental temperature to the evolution of pesticide resistance and infer the impacts of global warming on pesticide efficacy and future agricultural production and ecological sustainability. We achieved this by comparing azoxystrobin sensitivity of 180 P. infestans isolates sampled from nine geographic locations in China under five temperature schemes ranging from 13 to 25°C. We found that local air temperature contributed greatly to the difference of azoxystrobin tolerance among geographic populations of the pathogen. Both among-population and within-population variations in azoxystrobin tolerance increased as experimental temperatures increased. We also found that isolates with higher azoxystrobin tolerance adapted to a broader thermal niche. These results suggest that global warming may enhance the risk of developing pesticide resistance in plant pathogens and highlight the increased challenges of administering pesticides for effective management of plant diseases to support agricultural production and ecological sustainability under future thermal conditions.
Evolutionary Applications, 14(5), 1274-1285.
Keywords: Dun-Chun He; Abdul Waheed; Oswald Nkurikiyimfura; Zhen Wang; Li-Ping Shang; Li-Na Yang